2002
DOI: 10.1007/s00586-001-0366-6
|View full text |Cite
|
Sign up to set email alerts
|

Classificational problems in ligamentary distraction type vertebral fractures: 30% of all B-type fractures are initially unrecognised

Abstract: The clinical records, operation records, X-rays and CT-scans of 160 operatively treated patients with A-type and B-type spinal fractures were evaluated in a retrospective study. The preoperative diagnosis was compared with the postoperative diagnosis. Analysis of characteristics of patients with A-type fractures (without the unrecognised B-type fractures), initially unrecognised B-type (uB) fractures, and B-type fractures (without the unrecognised B-type fractures) was performed. We analysed the age of the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
30
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 22 publications
2
30
0
2
Order By: Relevance
“…As expected, most of the spine fractures occur at the thoracolumbar junction Th11-L2 and this is simply a reflection of the most common location of compression type fractures. In the patient population only two AO type B fractures are found, but as described in literature it could be possible that other AO type B fractures, especially those with ligamentous posterior injuries, were not diagnosed because MRI was not routinely performed [27]. As expected, average LSC scores are significantly higher for the surgically stabilized patients.…”
Section: Discussionsupporting
confidence: 51%
“…As expected, most of the spine fractures occur at the thoracolumbar junction Th11-L2 and this is simply a reflection of the most common location of compression type fractures. In the patient population only two AO type B fractures are found, but as described in literature it could be possible that other AO type B fractures, especially those with ligamentous posterior injuries, were not diagnosed because MRI was not routinely performed [27]. As expected, average LSC scores are significantly higher for the surgically stabilized patients.…”
Section: Discussionsupporting
confidence: 51%
“…As the designers of the AO classification have stated, some type B injuries are missed and classified as type A when only standard radiographs are available [9]. In their study, Leferink et al [8] found that 30% of type B fractures were unrecognized using traditional examination tools. The results of MRI changed our initial planned treatment in five patients, moving from a conservative to a surgical approach.…”
Section: Discussionmentioning
confidence: 99%
“…Early classifications were designed through the analysis of plain X-rays and CT scan, which are examination tools not completely able to show soft tissue anatomy [8,10,11,13]. With these, the suspicion of ligament injury has to be assessed by indirect indicators such as focal kyphosis, interspinous spacing, diastasis of the facet joints or more than 50% of anterior body compression [2,16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, it has been demonstrated that distinguishing between these two fracture types based on radiographs and computed tomography alone is unreliable. 4,5 Finally, no correlation data between the two classification systems were presented, leaving the primary research question unanswered. The midsagittal diameter (MSD) of the spinal canal was measured to assess the degree of canal narrowing.…”
mentioning
confidence: 99%